Depression and PTSD in Pashtun Women in Kandahar, Afghanistan - Sung-Man Shin, DSc; Hyun Jeong Kim, DClinPsy; Lina Liw, BA; Sungjae Kim, PhD, PMHNP, RN (Asian Nursing Research, 2009)
The objectives were (a) to establish prevalence of depression and post-traumatic stress disorder (PTSD) in Afghanistan and, (b) to investigate sociodemographic and quality of life variables, which predict depression and PTSD. Methods: Translated versions of the Beck Depression Inventory, Impact of Event Scale-Revised, and Quality of Life Inventory were administered to 125 Pashtun women in Kandahar, and statistically analyzed. Results: Approximately half of the participants showed moderate to severe levels of depression, and more than half of the participants exhibited symptoms of PTSD. Education and income showed significant associations with PTSD symptoms or depression. The way one spends time, general health status, and general feeling towards life predicted low levels of depression and PTSD. Conclusions: The high prevalence of depression and PTSD indicate the continuing need for mental health intervention. While education has been found to be a protective factor for mental health in previous studies, the relationship between education and mental health appear to be more complex among Afghan women. Quality of life variables could be further investigated and incorporated into mental health interventions for Afghan women.